Relationship between Prolactin, Chronic Kidney Disease, and Cardiovascular Risk - Marclébio Dourado; Frederico Cavalcanti; Lucio Vilar; Amaury Cantilino (International Journal of Endocrinology)
CKD has a high prevalence worldwide, mainly due to its main etiologies—diabetes and hypertension. It has high cardiovascular morbidity and mortality, with traditional risk factors such as atherosclerosis, hypertension, diabetes, smoking, and left ventricular hypertrophy being common. Nontraditional cardiovascular risk factors, such as anemia, hyperparathyroidism, chronic inflammation, and microalbuminuria, are also well studied. Prolactin is a hormone not only related to lactation but also being considered a uremic toxin by some authors. It accumulates with loss of renal function, and it is associated with cardiovascular outcomes in both normal renal function population and CKD population. The purpose of this narrative review is to raise the main common aspects of CKD, prolactinemia, and cardiovascular risk.